Convergence of ion channel genome content in early animal evolution - Liebeskind, Benjamin J. (Proc Natl Acad Sci U S A, 2015)
Multicellularity has evolved multiple times, but animals are the only multicellular lineage with nervous systems. This fact implies that the origin of nervous systems was an unlikely event, yet recent comparisons among extant taxa suggest that animal nervous systems may have evolved multiple times independently. Here, we use ancestral gene content reconstruction to track the timing of gene family expansions for the major families of ion-channel proteins that drive nervous system function. We find that animals with nervous systems have broadly similar complements of ion-channel types but that these complements likely evolved independently. We also find that ion-channel gene family evolution has included large loss events, two of which were immediately followed by rounds of duplication. Ctenophores, cnidarians, and bilaterians underwent independent bouts of gene expansion in channel families involved in synaptic transmission and action potential shaping. We suggest that expansions of these family types may represent a genomic signature of expanding nervous system complexity. Ancestral nodes in which nervous systems are currently hypothesized to have originated did not experience large expansions, making it difficult to distinguish among competing hypotheses of nervous system origins and suggesting that the origin of nerves was not attended by an immediate burst of complexity. Rather, the evolution of nervous system complexity appears to resemble a slow fuse in stem animals followed by many independent bouts of gene gain and loss.